Bolstering firm growth : Kasvu Open 2014 - Helin, Erik; Kangasvieri, Teemu (2015)
There has been a significant increase in SME growth research in recent years as its macroeconomic effect has become better understood. Firm growth has a significant influence on national economic health, especially small economies such as Finland, yet scholars agree that little is known about the phenomena. Authors of this study aim deliver a broader and more holistic approach to firm growth research and integrate currently fragmented constructs. By studying participants of Kasvu Open 2014, this study contributes to firm growth research by providing a new and unique context. Existing firm growth research has examined the effect of growth intention on firm growth, but few studies have addressed causal relationships between resources and growth intention. This study provides new insight to this relationship by measuring the effect of three types of resources on growth intention and in turn its effect on growth. The effect of growth intention on firm growth was also examined. To better understand firm growth, the study hypothesized that a firm’s internationalization ability affects firm growth, firm location in a cluster leads to growth, and that new ownership positively affects firm growth. Several quantitative analysis tools were used to understand these relationships and avoid methodological biases. Using a linear regression analysis, the study provides empirical evidence that availability of financial resources has a positive effect on growth intention. Additionally, results validate prior research and demonstrate that increased growth intention indeed bolsters firm growth. Results on the effect of a firm’s internationalization ability growth were inconclusive as were the suggested benefits of a cluster location. However, several findings were found to support existing literature.